A Study on the Changes of Urban Vista in Rattanakosin Area - Sourachai, Tharadol (Journal of Architectural/Planning Research and Studies (JARS), 2018)
This study aims to analyze the changes of urban vista within Krung Rattanakosin area by comparing past and present photographs and foreseeing the prospective vistas by using the visualization method with computer technique which is carried out through the current economics, social and political status affecting the changes of urban vista. This is done in parallel with the review on ideas, theories and techniques used in preserving to sustainable protect the valuable urban vistas. According to the comparative study of some urban vistas of 53 important sites, it is found that changes occur due to two main reasons: the internal factors resulting from proprietors and the external factors, affecting from the other places within visual field. Most of these changes arise from the conversion addition, deterioration and demolition of physical structures that subsequently brought about the appearance in the background, the visual disturbance and blocking of buildings or other structures. The analysis of computer modeling to foresee the prospective changes reveals that the urban vistas in Krung Rattanakosin area could potentially be more disturbed. The main idea that could possibly eliminate the negative changes of urban vistas within Krung Rattanakosin area is to confer a proper understanding and realization on the importance of urban vistas for all concerned parties. Additionally, the processes, mechanisms and measures for systematically conserving of the valuable urban vistas should be crucially improved.